The impact of role models on entrepreneurial intentions and behavior: a review of the literature - Arezou Abbasianchavari; Alexandra Moritz (Management Review Quarterly, 2020)
Despite the presence of the term `entrepreneurial role model' (ERM) in the discourse on entrepreneurship, existing empirical evidence on the effects of role models is rather limited. By investigating 86 published journal articles, we provide a structured overview of the academic research on role models' effects on entrepreneurial intentions and behavior. We reveal that prior research focuses particularly on different types of role models (by whom), at which stage of life (when) and in which context the exposure to role models occurs. We use these research areas to structure our review. By expanding the understanding of the current state of ERM research, we reveal research gaps and provide future research recommendations. Our work could help policy makers and educators consider the different types of role models, the sociocultural context and the life cycle stage of the participants in structuring their entrepreneurship education programs.
Keywords: 650; Entrepreneurial role model; Entrepreneurial intentions; Entrepreneurial behavior; Entrepreneurship; Literature review